STRATEGI POSITIONING OPERATOR TELEPON SELULER GSM SISTEM PRABAYAR BERDASARKAN PERSEPSI KONSUMEN di KOTA SUKABUMI: Manajemen pemasaran - ENDANG NARYONO, SE., MM (Ekonomedia, 2017)
This study aims to analyze the positioning map of GSM mobile telephone operators prepaid systems based on consumer perception in the city of Jember. The basis used to position cellular telephone operators is consumers' perceptions of the similarity of the determinant attributes consisting of products, prices, promotions, location, processes, people, and physical evidence of each cell phone operator. The analysis technique is Multidimensional Scaling (MDS). This research was conducted by taking 60 respondents with a purposive sampling method. The data obtained were tested using MDS analysis to determine the reliability and validity, the results of positioning maps of GSM cell phone operators of prepaid systems (Telkomsel, Indosat, XL, 3, and AXIS) based on consumer perceptions, and the similarity of respondents' attitudes in providing ratings . Based on the resultsof the analysis there are differences in the position of each GSM cell phone operator prepaid system based on consumer perception and shows that the GSM cell phone operator of the AXIS prepaid system is the closest competitor or direct competitor of the Telkomsel brand, especially regarding promotion, location, and process. XL and Three operators do not have direct competitors (indirect competitors) because they have the biggest difference or clear and unique differentiation. Indosat operators do not have a strong or clear positioning, because they do not have many similarities and also do not have much difference with other operators in the minds of consumers. The results of the consistency test and the similarity of the respondents' attitudes also showed that the respondents did not have the same attitudes in assessing the similarity of GSM prepaid cell phone operators.